Direct effects of phosphorylation on the preferred backbone conformation of peptides: a nuclear magnetic resonance study - Tholey, Andreas; Kinzel, Volker; Reed, Jennifer (Biophysical journal, 2009)
Control of protein activity by phosphorylation appears to work principally by inducing conformational change, but the mechanisms so far reported are dependent on the structural context in which phosphorylation occurs. As the activity of many small peptides is also regulated by phosphorylation, we decided to investigate possible direct consequences of this on the preferred backbone conformation. We have performed 1H nuclear magnetic resonance (NMR) experiments with short model peptides of the pattern Gly-Ser-Xaa-Ser, where Xaa represents Ser, Thr, or Tyr in either phosphorylated or unphosphorylated form and with either free or blocked amino and carboxy termini. The chemical shifts of amide protons and the 3JNH-Hα coupling constants were estimated from one-dimensional and two-dimensional scalar correlated spectroscopy (COSY) spectra at different pH values. The results clearly indicate a direct structural effect of serine and threonine phosphorylation on the preferred backbone dihedrals independent of the presence of charged groups in the surrounding sequence. Tyrosine phosphorylation does not induce such a charge-independent effect. Additionally, experiments with p-fluoro- and p-nitro-phenylalanine-containing peptides showed that the mere presence of an electronegative group on the aromatic ring of tyrosine does not produce direct structural effects. In the case of serine and threonine phosphorylation a strong dependence of the conformational shift on the protonation level of the phosphoryl group could be observed, showing that phosphorylation induces the strongest effect in its dianionic, i.e., physiological, form. The data reveal a hitherto unknown mechanism that may be added to the repertoire of conformational control of peptides and proteins by phosphorylation.
Available online 6 January 2009
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 02.03.2021